The Intel microprocessors : 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, Pentium Pro processor, Pentium II, Pentium III, Pentium 4, and Core2 with 64-bit extensions : architecture, programming, and interfacing - Brey, Barry B. (Pearson Prentice Hall, 2009)
"Knowledge of Intel microprocessors, found in most computer systems and in many areas of electronic communications and control systems, is essential for a career in electronics, computer science, or any field that relies on computer systems. Now in its eighth edition, The Intel Microprocessors provides updated comprehensive coverage of the latest developments in the field of microprocessors."--BOOK JACKET.